Varied clinical presentations of scar endometriosis: case reports - Gupta, Nidhi; Mazhari, Farhat; Varun, Neha; Tripathi, Reva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Endometriosis is the second most prevalent benign gynaecological condition, in reproductive age women, defined as the presence of functioning endometrial tissue outside uterine cavity. Scar endometriosis is a rare entity with an incidence of 0.3-1% among reproductive age women following obstetric and gynaecologic surgeries. Complaints of pain, tender mass, cyclical association with menstrual cycle is almost pathognomonic. Here we present two case reports of scar endometriosis recently encountered at our institute – caesarean scar endometriosis and episiotomy scar endometriosis. The quoted episiotomy scar endometriosis incidence is about 0.06 - 0.07% while that of caesarean scar endometriosis is 0.03-0.4%.